145 Application of graphene based coating on coronary artery stents. (5th June 2017) - Jafarzadeh, Fatemeh; McManus, Daryl; Barbolina, Irina; Malik, Nadim; Casiraghi, Cinzia; Holt, Cathy
Abstract : Coronary artery disease is the leading cause of death worldwide. Stent implantation is the mainstay approach to revascularise stenosed coronary arteries. Bare metal stents were the first stents designed, but presented a restenosis risk of approximately 20% of patients due to restenosis. Subsequently, drug eluting stents were introduced, which, however, introduced late in stent thrombosis. We propose the use of a graphene based coating onto bare metal stents in an attempt to significantly reduce stent associated complications and promote vessel healing. Graphene is a single layer of carbon atoms arranged in a honeycomb lattice. The unique properties of graphene make it an ideal material to use as an implantable device coating: It has a high surface to volume ratio; it is impermeable and atomically smooth and has been shown to exhibit bio-compatible properties. Graphene based dispersions were prepared by liquid phase exfoliation in water. Investigations to coat bare metal stents were undertaken. Dip, spin and spray coating methods were explored. Raman spectroscopy was measured to identify and characterise the coated material. Raman spectroscopy demonstrated spray coating to result in the most uniform and thin graphene based coating. In addition, human endothelial cell adherence and proliferation on the graphene based coating was studied. Hoechst 33 342 and phalloidin stains were used to image the cells under fluorescence microscopy. This revealed the adherence of human endothelial cells to be unaffected by the graphene based coating. In conclusion, spray coating created the most uniform and thin graphene based coating onto bare metal stents. Human coronary artery endothelial cell adherence occurred on the graphene coated stents. Future work is aimed at studying bio- and haemo- compatibility of graphene based coating and their performance in a porcine stent model.